Profile of vitamin D in a cohort of physicians and diabetologists in Kolkata - Arjun Baidya; Subhankar Chowdhury; Satinath Mukhopadhyay; Sujoy Ghosh (Indian Journal of Endocrinology and Metabolism, 2012)
Introduction: Vitamin D deficiency has been documented across all age groups and both sexes from India. However, there is paucity of data on vitamin D deficiency in a particular cohort of population. Objectives: To assess the vitamin D status in a cohort of physicians and diabetologists in Kolkata. Material and Methods: An observational cross sectional study carried out in the month of December 2011 in a cohort of 40 physicians and diabetologists in Kolkata. Results: A total of 40 subjects were studied. Mean age of the cohort was 52.22 ± 10.91.Mean serum vitamin D level was 13.02 ± 4.77 ng/ml. Nearly 92.5% and 5.0% of subjects had vitamin D deficiency and insufficiency, respectively. Conclusions : Vitamin D deficiency is highly prevalent in physicians and diabetologists in Kolkata.